Identification of Determinants Entrepreneurial Intentions during the Covid Pandemic on Open Unemployment in Tasikmalaya - Nanang Rusliana; Aquinaldo Sistanto Putra; Encang Kadarisman (Universitas Islam Kadiri, 2023)
During the Covid-19 pandemic, the business sector experienced a slowdown due to declining purchasing power. Dozens of companies had their revenue decline, forcing them to focus on cost efficiencies, including laying off workers. As a result, the unemployment rate has surged. Becoming an entrepreneur is a viable option to generate income for those who are unemployed. This research aims to identify the factors driving individual motivation to become entrepreneurs in adverse conditions, especially during a pandemic. The conceptual model employed in this research was modified from the Theory of Planned Behavior by adding resilience as an additional independent variable. Using simple random sampling for sample selection, a total of 225 respondents who live in Tasikmalaya City and Tasikmalaya Regency participated in this study. The multiple linear regression methods was deployed for further analysis and hypothesis testing. The results reveal that the formation of entrepreneurial intentions in the unemployed in Tasikmalaya City and Tasikmalaya Regency is influenced by attitudes, subjective norms, perceptions of behavioral control, and resilience.